Shake O' Nut / Muhammad Ihsan Sharulizam - Sharulizam, Muhammad Ihsan (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
The product name is Shake o Nut. "Shake o Nut" is a snack. So, what is Shake o Nut? The name' shake o nut ' refer to the concept of the product which requires customers to shake the product before enjoying it. So that is why, my product description is shake nut snack. The tag line product which is taste of fun. So why A taste of fun? This is because the process of enjoying is fun since customer need to shake and enjoy. Secondly a taste of fun also refers to the fun flavor makes the customer happy and enjoy to eat. "Shake o Nut" introduce 3 flavors. The flavors cheesy almond, Salted pistachio, and the highly recommended one the spicy walnut. It is a new range of product produced by a local company called "Kacang Goncang treading". Kacang Goncang started around 2020 in the area of Kuala Lumpur. The founder of this company is Aidil lzham. Shake o Nut goals is to inspire many Malaysia to enjoy eating snack in a fun away. It's also time for local product to have more recognitions with the new innovations of local taste and flavors. The funky colors and cheerful design concept of the product is specifically to targeted young generations which is more up-to-date with the current trend and lifestyle. There is a lot of competitors regardless of local or international brands in today's market. Some of it are popular product such as Twisties-Chacho's, Doritos, Mister Potato, Pringles and Mission. All of it has their own brand strategy. The design concepts for Shake o Nut is creative, fun and funky look to meet the lifestyle of the modern era. The design uses bright colors such as bright green, strong orange and hot red to highlight each new flavor to make the main ingredients look bolder and stand up. As a designer for this product, I am truly satisfied with the overall look and feel of this product. I believed that Shake o Nut will go as far other famous brands in Malaysia and to be a formidable opponent. Shake O Nut, a taste of fun!